PAID-PL—The Polish Version of the Problem Areas in Diabetes Scale: Perfect Reliability and a One-Factor Structure - Cichoń E (Dove Medical Press, 2021)
Ewelina Cichoń,1,2 Andrzej Kiejna,1,2 Tomasz M Gondek,3,4 Marcin Obrębski,5 Edyta Sutkowska,6 Cathy E Lloyd,7 Norman Sartorius,8 Andrzej Kokoszka5 1Department of Psychology, WSB University in Torun, Torun, Wroclaw, Poland; 2Department of Psychology, Faculty of Applied Studies, University of Lower Silesia, Wroclaw, Poland; 3Specialty Training Section, Polish Psychiatric Association, Wroclaw, Poland; 4Section on Education, World Psychiatric Association, Wroclaw, Poland; 5II Department of Psychiatry, Medical University of Warsaw, Warsaw, Poland; 6Department and Division of Medical Rehabilitation, Wroclaw Medical University, Wroclaw, Poland; 7Faculty of Health and Social Care, The Open University, Milton Keynes, UK; 8Association for the Improvement of Mental Health Programmes (AIMH), Geneva, SwitzerlandCorrespondence: Andrzej KokoszkaII Department of Psychiatry, Medical University of Warsaw, 03-242 Kondratowicza 8 street, Warsaw, PolandTel/Fax +48 22 326 58 92Email andrzej.kokoszka@wum.edu.plPurpose: The aim of this study was to assess the structure and validate the Polish version of the Problem Areas in Diabetes (PAID) scale, as the current translations of the original English version significantly vary in their psychometric properties.Patients and Methods: Two hundred and sixteen consecutive Polish outpatients were invited to participate in this international cross-sectional study on depression in diabetes. The research was based on the demographic and clinical characteristics of the study population, including the level of glycated hemoglobin (HbA1c) and scores obtained in the Polish versions of the following questionnaires: PAID, World Health Organization-Five Well-Being Index (WHO-5), Patient Health Questionnaire 9 (PHQ-9). The psychiatric diagnosis was conducted with the use of Mini-International Neuropsychiatric Interview (M.I.N.I.).Results: Exploratory factor analyses yielded a 1-factor structure that included all 20 items. The internal consistency of the Polish version of PAID was high (Cronbach α = 0.97). There were significant positive correlation between PAID and PHQ-9 and a negative correlation between PAID and WHO-5. We also observed a negative association between PAID scores and age and a positive correlation between PAID and HbA1c levels. Patients with depression reported significantly higher PAID scores as compared with those without depressive symptoms.Conclusion: The Polish version of PAID has a one-factor structure and is a reliable, valid outcome measure for Polish outpatients with type 2 diabetes and it may constitute a useful instrument for screening for psychologic issues in diabetic patients during their appointments at the diabetes clinic.Keywords: diabetes mellitus, type 2, emotional stress, depression, quality of life, problem areas in diabetes scale